Étude du comportement mécanique d’une reliure de la fin du XVe siècle – Le Missel de Cambrai - Lara Meersseman (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The article concerns the restoration of an incunabula printed in 1495 in Paris. Our goal was to adapt our interventions taking into account the various constituent materials of the medieval book: leather, wood, sewing and fittings. The techniques used aim at stabilizing degradation and strengthening the mechanical structure while maintaining historical and structural integrity of the Missal.